PERTUMBUHAN UMKM TERHADAP EKONOMI PEMBANGUNAN DI SUMATERA UTARA - Adinda Arafah; Suci Ramadhini (CV. ADIBA AISHA AMIRA, 2023)
Growth in today's globalized world is typically gauged by how well the government manages the economy. The importance of Micro, Small, and Medium-Sized Enterprises (MSMEs) to national development, especially economic development, cannot be overstated. Small and medium-sized enterprises (SMEs) play a crucial and strategic role in the national economy. There has been a consistent annual growth in post-crisis MSMEs. That MSMEs can weather a financial storm is further evidence of this. There is also evidence that shows MSMEs absorb a disproportionate share of the national labor force. The MSME sector is able to raise wages because it employs so many people. This means that micro, small, and medium-sized enterprises (MSMEs) play a crucial part in fighting poverty and unemployment. To maximize the impact of MSMEs on the national economy's growth, it's crucial that the government maintains its current level of support for the sector. The methods and literature used in this study are qualitative in nature, drawing from a wide range of sources. Findings indicate that syntactic, semantic, and pragmatic methods can be used to ascertain MSMEs' impact on the framework of economic theory. Small and medium-sized enterprises (SMEs) exert power in three ways: syntactically, via the rules that define them; semantically, via their connection to the underlying economic reality; and pragmatically, via their use by investors who don't care about how it is measured or what it means